Contamination of chicken meat with extended-spectrum beta-lactamase producing- Klebsiella pneumoniae and Escherichia coli during scalding and defeathering of broiler carcasses. (February 2019) - Projahn, Michaela; von Tippelskirch, Philine; Semmler, Torsten; Guenther, Sebastian; Alter, Thomas; Roesler, Uwe
Abstract: Extended-spectrum beta-lactamase- (ESBL-) producing Klebsiella (K.) pneumoniae and Escherichia (E.) coli are of critical importance in human and veterinary medicine. Animal food products, especially broiler chickens, are discussed as a possible source for the exposure of humans with antibiotic resistant bacteria. Although the occurrence and vertical transmission of ESBL-/AmpC-producing Enterobacteriaceae in the broiler production has been reported before, detailed investigations concerning the dissemination along the slaughter processing line are missing. In this study, we investigated cross-contamination with ESBL-producing Enterobacteriaceae during the processing of two different broiler flocks in one slaughterhouse. The ESBL-status during the fattening period of the flocks was determined and environmental samples from the slaughterhouse were taken before processing of the respective flocks. These isolates were compared to those found in samples from the carcasses after processing using whole genome sequencing. Phylogenetic analyses of seven ESBL-producing K. pneumoniae and 14 E . coli revealed close relationships between isolates from scalding water and the defeathering machine, respectively, which were collected before the processing of the broiler flocks, to those isolates found in samples from skin and filet of the respective flock carcasses. In conclusion, using high resolution molecular data we found evidence for the cross-contamination of carcasses with ESBL-producing Enterobacteriaceae during scalding and defeathering in the slaughterhouse. Highlights: Cross-contamination with ESBL-producing potential pathogenic strains was shown by WGS. Chicken meat from originally ESBL-free broilers became contaminated in the slaughterhouse. Scalding and defeathering were critical contamination steps during carcass processing.